Diseño de un modelo de estructura organizacional que permita incluir a la población en situación de discapacidad a través de sus capacidades y habilidades tanto trabajadores como clientes en el sector de restaurantes (2014)
This research paper aims to present the design of a model of employment and social inclusion of people with disabilities, as employees and customers through their skills and capabilities, applied in different jobs, generating facilitators allow them to be included in society. The proposed research aims, by applying principles of industrial engineering, create a model of employment and social inclusion for people living with disabilities, to articulate the development of human talent with the social needs of this population to promote development of their abilities, skills and satisfaction of needs in society.